ANALISIS YURIDIS MENGENAI BENTUK PERLINDUNGAN RAHASIA BANK DAN SANKSI TERHADAP PELANGGARAN RAHASIA BANK - Manurung, Darwis (Universitas Borneo Tarakan, 2024)
Banking is everything that concerns about banks, including institutional, business activities, as well as the manner and process of operation. To avoid misuse of customer financial hence made a special rule that prohibits banks to provide recorded information to anyone associated with the customer's financial situation, savings and storage as set out in Pasal 1 angka 28 Undang-Undang Nomor 10 Tahun 1998 tentang Perubahan Atas Undang-Undang Nomor 7 Tahun 1992 tentang Perbankan, which states that bank secrecy is everything related to the storage of information about your customers and their savings. The purpose of this thesis is to investigate the problems Banking Act already provides legal certainty regarding the form of protection that is done by the banks to protect confidential client or not, as well as the Banking Act already provides legal certainty in terms of sanctions for the banks were negligent inmaintaining banking secrecy or not.This type of research can be classified into types of normative legal research, since the study was conducted by collecting data in the literature (library research) accompanied by collecting data and read through regulatory references, magazines, the internet and other sources, and then selected the data - the data is worth to support writing.From the research problem there are 2 main things that can be inferred. First, the Banking Act not provide legal certainty regarding the form of bank secrecy protection carried out by the bank in secrecy customers. Second, the Banking Act not provide legal certainty in terms of sanctions for the banks were negligent in maintaining banking secrecy. Suggestions Author, First, the need for the addition of a form of protection provided by the banks to customers about the confidentiality of Undang-Undang Nomor 10 Tahun 1998 tentang Perubahan Atas Undang-Undang Nomor 7 Tahun 1992 tentang Perbankan, in order to create legal certainty and confidence to guarantee customers in saving money in any bank. Secondly, a need for the addition in the field of civil and criminal penalties to protect customers who are weak in Undang-Undang Nomor 10 Tahun 1998 tentang Perubahan Atas Undang-Undang Nomor 7 Tahun 1992 tentang Perbankan, in order to create legal certainty and confidence guarantee for customers in saving funds at any bank.Keywords: Protection-Sanctions-Secret Bank